CZY KULTURA WŁASNA JEST POTRZEBNA DO ROZWIJANIA KOMPETENCJI (INTER)KULTUROWEJ? O UWZGLĘDNIANIU KULTURY OJCZYSTEJ W PROCESIE NAUCZANIA/UCZENIA SIĘ JĘZYKA OBCEGO - Waszau, Anna (Neofilolog, 2020)
The purpose of the present article to reflect on the possibilities of developing (inter)cultural competence in the context of glottodidactics by resorting to elements of the source culture, which helps to build (meta)cultural awareness. By analyzing from a diachronic perspective, together with some traditional approaches and modern concepts, it is shown that the evolution of glottodidactic models indicates the need to develop a reflective attitude which is built upon the (meta)cultural awareness. This progress, in turn, requires reflection on one’s cultural identity and on the system of one’s own culture which influences the socialization and enculturation processes. Therefore, awareness thus conceptualized can help in determining and understanding the organizational and generative principles of cultures, as well as their functioning and mechanisms.